THE EFFECT OF ANALGESICS COMBINATION OF PARACETAMOL AND CODEINE ADMINISTRATION TO SERUM UREA IN MALE WISTAR RATS - Akhiar Mar'i; Taufik Eko Nugroho; Erwin Kresnoadi; Parish Budiono (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: A combination of the analgesic drug Paracetamol and Codeine can be used in moderate to severe pain management. Both are classified into two different groups of analgesics, thus they have a different mechanism of action. The combination of Paracetamol and Codeine provides better potential and work synergistically in pain management. This combination of analgesic drugs also has no potential side effects on the kidneys. Objective: To determine the combination of paracetamol and codeine analgesics on serum urea levels in male Wistar rats. Method: This study is an experimental study with a Post Test Only Control Group Design. Samples were 20 Wistar rats with certain criteria, randomly divided into 4 groups: control group, 32 mg/kgBW paracetamol group, 1,9 mg/kgBW codeine group, and 32 mg/kgBW paracetamol combination group and codeine 1,9 mg/kgBW. Giving is done orally with gastric sonde 4 times a day for 28 days. Day 29, blood is drawn through retroorbital vessels to measure serum urea levels. Statistical tests using the ANOVA and Post-Hoc tests. Results: The results obtained by the control group (32.1880), treatment group 1 (32.4240), treatment group 2 (32.3000), and treatment group 3 (31.1560). The One Way ANOVA statistical test results showed that the value of p = 0.970 (p> 0.05) which means there are no significant differences in serum urea levels between the four groups. Conclusion: There was no significant difference in the increase in the urea level between the combination of paracetamol and codeine compared to the control group.